Application of next generation sequencing for the elucidation of genes and pathways involved in the host response to bovine respiratory syncytial virus. Issue Volume 1(2019)Issue A (8th March 2019) - Johnston, Dayle; Earley, Bernadette; McCabe, Matthew; Blackshields, Gordon; Lemon, Ken; Duffy, Catherine; McMenamy, Michael; Cosby, Sara Louise; Kim, Jaewoo; Taylor, Jerry; Waters, Sinead
Abstract : High rates of calf mortality in the first 12 months of life, results in significant economic losses in Europe and the USA. Bovine respiratory disease (BRD) accounts for the largest proportion of calf mortality. There is a paucity of literature concerning the host response to BRD. In a controlled challenge study in artificially reared dairy calves [155 (S.D. 14) kg], the influence of the host response to bovine respiratory syncytial virus (BRSV) was examined. At AFBI Holstein-Friesian calves were either challenged with BRSV ( n =12) or mock challenged with phosphate buffer saline ( n =6). Calves were euthanised on day 7 post-challenge. Bronchial lymph nodes were collected and flash-frozen at −80 °C. RNA was extracted and sent to the University of Missouri's DNA Core Facility for RNA-Seq library preparation and sequencing. Sequenced reads were adapter trimmed, quality assessed using FastQC and aligned to the bovine genome (UMD 3.1) using STAR. Differential gene expression analysis was performed using EdgeR, and pathway and gene ontology analyses were carried out using g:Profiler and Ingenuity Pathway Analysis (IPA). There was a clear separation between BRSV challenged and control calves based on log2 fold gene expression changes, despite an observed mild clinical manifestation of the disease. There were 934 differentially expressed genes (DEG) ( P <0.05, FDR<0.1, fold change >2) between the BRSV challenged and control calves. Over-represented pathways and gene ontology terms among the DEG were associated with immune responses and included: GO:0051607 defense response to virus, the KEGG pathway Influenza A and the IPA pathway Interferon Signaling.